Validity and reliability of the Korean version of the gender-friendliness barriers in nursing programs scale - Park, Seon-Min; Kim, Jung-Hee (Frontiers in Psychology, 2023)
The Gender-friendliness barriers in nursing programs (GFB-NP) were used to measure perceived gender affinity among male nursing students in nursing education programs. A shift in social attitudes has led to an increase in the number of male nursing students and male nurses, as well as a demand for their nursing services. Studies have identified the requirements of male nurses and the factors influencing their satisfaction. Hence, it is necessary to clarify the reliability and validity of the GFB-NP scale for male nursing students in Korea, considering the culturally distinct context. The Korean version of the GFB-NP was used to assess perceived gender affinity among male nursing students in nursing education programs. A convenience sample of male nursing students enrolled in the 1st to 4th year of nursing departments at five four-year universities located in three cities in Korea was used in the study. To confirm the validity and factor structure of the scale, both exploratory factor analysis and confirmatory factor analysis were employed. The results support a four-factor structure: Professional acquisition opportunity, Peer interaction, Sociocultural prejudice, and Gender role attitude. We confirmed that the Korean version of the GFB-NP is an appropriate tool for measuring the gender-friendliness educational environment perceived by male nursing students in nursing education.